Adrenergic, Coagulation, and Fibrinolytic Responses to Heat. Issue 5937 (19th October 1974) - Britton, B. J.; Hawkey, Christine; Wood, W. G.; Peele, Muriel; Kaye, J.; Irving, M. H.
Abstract : Two groups of volunteers were exposed to heat in a sauna bath—one group for 10 minutes and the other for 15. There was no change in plasma adrenaline concentration until the subjects emerged from the sauna bath, when there was a slight increase in concentration. Factor VIII and thrombo-elastograph patterns did not change but marked activation of fibrinolysis was stimulated by exposure to heat. These findings support the concept that fibrinolysis is not mediated by direct adrenergic activity.